2014
DOI: 10.1073/pnas.1410480111
|View full text |Cite
|
Sign up to set email alerts
|

Climate change decouples oceanic primary and export productivity and organic carbon burial

Abstract: Understanding responses of oceanic primary productivity, carbon export, and burial to climate change is essential for model-based projection of biological feedbacks in a high-CO2 world. Here we compare estimates of productivity based on the composition of fossil diatom floras with organic carbon burial off Oregon in the Northeast Pacific across a large climatic transition at the last glacial termination. Although estimated primary productivity was highest during the Last Glacial Maximum, carbon burial was lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 36 publications
4
42
1
Order By: Relevance
“…Table 2 gives an overview of some trends in C burial depending on the climate condition change between main glacial and interglacial. Lopes et al (2015) found just the opposite in ocean sediment layers produced during the warm interstadial compared to the cold main glacial, i.e., a high burial rate of organic C in the ocean bottom sediment. But in spite of the high organic C burial rate, the interstadial CO 2 levels were kept higher than those of the main glacial.…”
Section: Phytoplankton Fertilizer Extraction From Ocean Sediments Andmentioning
confidence: 79%
See 4 more Smart Citations
“…Table 2 gives an overview of some trends in C burial depending on the climate condition change between main glacial and interglacial. Lopes et al (2015) found just the opposite in ocean sediment layers produced during the warm interstadial compared to the cold main glacial, i.e., a high burial rate of organic C in the ocean bottom sediment. But in spite of the high organic C burial rate, the interstadial CO 2 levels were kept higher than those of the main glacial.…”
Section: Phytoplankton Fertilizer Extraction From Ocean Sediments Andmentioning
confidence: 79%
“…The ratio of organic C burial to carbonate C burial is much smaller than 1. The results of Lopes et al (2015) from northeast Pacific sediments demonstrate that, although primary productivity was estimated to be highest during the Last Glacial Maximum, organic C burial was lowest. This coincides with our proposed optimum mixed O 2 -rich milieu throughout the whole water column.…”
Section: Carbon Storage As Organic and Inorganic Marine Debris And Asmentioning
confidence: 96%
See 3 more Smart Citations